Technological forecasting : - Cetron, Marvin J. (Technology Forecasting Institute, 1969)
This book by Marvin Cetron is a "touchstone" which will serve to guide those who would desire meaningful forecasts and meaningful use of those forecasts. It is hoped that these chapters will encourage involvement and interest by planners at all levels in technological forecasting.